2016
DOI: 10.1589/jpts.28.2769
|View full text |Cite
|
Sign up to set email alerts
|

Immediate effects of forearm elastic and nonelastic taping on wrist flexor muscle and grip strength of normal adults

Abstract: [Purpose] The purpose of this study was to examine the effects of forearm elastic taping on grip and wrist flexor muscle strength. [Subjects and Methods] This was a single-blind, crossover study. This study selected 40 healthy subjects with no history of orthopedic disorders and was conducted after consent to participate was obtained. Grip and wrist flexor muscle strength of subjects were assessed by a handheld dynamometer and a Commander Muscle Tester, respectively, with forearm elastic taping or nonelastic t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 7 publications
0
4
0
1
Order By: Relevance
“…In females, it was observed that the increase in strength of 90 minutes was maximum (23.9%) (Mohammadi et al, 2014). In a study applied to forearm muscles in healthy individuals, they stated that Y-shape kinesio taping had positive effects on hand grip strength (Cha et al, 2016). In a study investigating the effect of the application direction of kinesio taping on hand grip strength in healthy female individuals, it was revealed that the taping from the bottom up (insersio to origo) was not effective in the perception of hand grip strength (Hosseini et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…In females, it was observed that the increase in strength of 90 minutes was maximum (23.9%) (Mohammadi et al, 2014). In a study applied to forearm muscles in healthy individuals, they stated that Y-shape kinesio taping had positive effects on hand grip strength (Cha et al, 2016). In a study investigating the effect of the application direction of kinesio taping on hand grip strength in healthy female individuals, it was revealed that the taping from the bottom up (insersio to origo) was not effective in the perception of hand grip strength (Hosseini et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The immediate effects of elastic tape application on maximal muscle strength in healthy individuals have conflicting results. While some studies have reported that elastic tape application increases hand grip and hip extensor strength 8 , 18 , 19 ) , others have demonstrated that it does not affect ankle dorsiflexion strength 8 ) . The lack of effects on PFS in this study may be attributed to two reasons.…”
Section: Discussionmentioning
confidence: 99%
“…First, the elastic tape was not applied to the major muscles responsible for plantar flexion of the ankle. In three previous studies that have reported increases in maximal muscle strength, an elastic tape was applied along the wrist extensors 18 , 19 ) and gluteus maximus 8 ) . The method used in this study which was the application of an elastic tape to the foot sole may not have sufficiently enhanced the strength of the triceps surae muscle that causes plantar flexion of the ankle.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study, taping on skin increased muscle activity and increased joint stability, thus protecting the joint by reducing pressure on it. Third, taping on skin right on the muscle restricts muscle hypertension by stimulating the agonist muscles and decreases local pain through neurological and dynamic stimulation 13 ) .…”
Section: Discussionmentioning
confidence: 99%